NFM-06. NF106: PHASE 2 TRIAL OF THE MEK INHIBITOR PD-0325901 IN ADOLESCENTS AND ADULTS WITH NF1-RELATED PLEXIFORM NEUROFIBROMAS: AN NF CLINICAL TRIALS CONSORTIUM STUDY. Issue 2 (22nd June 2018) - Weiss, Brian; Plotkin, Scott; Widemann, Brigitte; Tonsgard, James; Blakeley, Jaishri; Allen, Jeffrey; Schorry, Elizabeth; Korf, Bruce; Rosser, Tena; Goldman, Stewart; Vinks, Alexander; Cutter, Gary; et al.
Abstract: Plexiform neurofibromas (PNs) can cause significant disfigurement, compression of vital structures, neurologic dysfunction, and pain. MEK pathway inhibition results in significant PN shrinkage in neurofibromatosis type 1 (NF1) mouse models of PN. We evaluated the efficacy of the MEK inhibitor, PD0325901, in adolescents (≥ 16 years of age) and adults with symptomatic or growing NF1-PN in a phase II open label study. The primary aim was to assess tumor response by cycle 12 using centrally read MRI, defined as at least 20% decrease in tumor volume from baseline. Subjects received PD-0325901 by mouth twice daily at 2 mg/m2/dose (maximum dose 4 mg bid). Each course was 4 weeks, and subjects received drug on a 3 week on / 1 week off schedule. NF106 enrolled 19 subjects (7M;12F) in two stages with a median age of 24 years (range 16-39 years). The mean PN volume was 797.8 mL. Eight subjects (42.1%; 95% CI: 20%, 67%) had a response. PD0325901 was well tolerated, with the most common dose limiting toxicity being acneiform rash in 3/19 patients (16%). Five subjects (26.3%) developed Grade 3 toxicities, mostly pain (4/19; 21%). No subjects developed Grade 4 or higher toxicities. Five subjects (26.3%) had a dose reduction for toxicity: one for Grade 3 abdominal and back pain, the others for intolerable Grade 1-2 nausea, rash, or fatigue. This study demonstrated that PD0325901 is well tolerated and results in PN shrinkage in 42% of adolescent and adult subjects with NF1-PN. Supported by DOD Award W81XWH-12-1-0155.